Current state of mining and processing of bentonite clays of Uzbekistan and prospects for their application in the metallurgical industry of the Republic of Belarus - B. T. Sabirov (Литьë и металлургия)
The article presents data on the chemical composition of bentonite clays from various deposits in Uzbekistan. The feasibility of mixing bentonite clays from various deposits to obtain higher technological indicators is shown. It is proposed to conduct research to adapt bentonites to the conditions of their use in the foundry industry of Belarus.